Primary Pancreatic Hepatoid Carcinoma: A Case Report and Literature Review - Tyng-Wei Yang; Hsiang-Fong Kao* (Journal of Cancer Research and Practice)
Hepatoid carcinoma is a rare primary malignancy in the pancreas. We report a case with a long indolent course of primary pancreatic hepatoid carcinoma (PHC) before curative surgery, with an estimated doubling time of 429 days. After surgery, the patient took adjuvant TS-1 (tegafur, gimeracil, and oteracil). They did not have recurrence or metastases 9 months after surgery. We reported their pathological features. We review PHC’s clinical features, pathological diagnosis, and reported treatment experiences.